Defensive Architecturesduring The Neolithic periods,Case Study: The Ancient Arab Orient (Damascus University Journal of Historical Studies, 2024)
This research deals with the sites of defensive architectures  during The Neolithic Age, and the study area is limited to the ancient Arab East (the Levant and Iraq),With a simple comparison with some architectures sites in other geographic regions of the world.This research depends on its communication,which accumulates all sites in which defensive architectures have appeared in the Neolithic sites in  integrated only work.Which is an urgent need to understand the early root of the beginning of the defensive architectures in general.The research follows the descriptive approach in an analytical manner, andbegins with describing the sites where  defensive constructions appeared in each of the sites separately, in terms of their pattern, places of placement, and architectural structure.Finally, the analysis of the descriptive study  due  to answer the questions .  It  should be noted that the main source of information in this research is the  studies that dealt with the studied archaeological sites dating back to the Neolithic period
Keywords: The Neolithic Age; Defensive architectures; The Levant and Iraq; Arab orient